Review of Issues and Solutions in High-Power Semiconductor Laser Packaging Technology - Yan, Yixiong; Zheng, Yu; Sun, Haigang; Duan, Ji’an (Frontiers in Physics, 2021)
In the past 20 years, semiconductor lasers have been widely used in medical, industrial, and communication applications, providing a revolutionary and powerful platform for the fifth generation and advanced manufacturing. Semiconductor laser has the advantages of small size, lightweight, high reliability and easy modulation, becoming increasingly popular. However, due to the laser diode emission mechanism limitation, the beam quality is inferior and cannot be directly applied and required to be handled by beam shaping. However, the packaging of multiple beam shaping optical components is accompanied by risks due to misalignment. The misalignment error of the optical components has a great hidden danger to the laser performance. As semiconductor lasers' power gradually increases, lasers' thermal management technology is also increasingly strict. Therefore, this article first reviews the beam shaping technology of semiconductor laser diode array. Secondly, the analysis of the influence of the array semiconductor laser optical device's misalignment is reviewed, and a feasible solution is proposed. Finally, it summarizes the researches on thermal management in high-power semiconductor lasers. This article aims to give readers a comprehensive and broad understanding of semiconductor laser packaging's technical difficulties and to recognize each corresponding solution.